(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
Shodhana (purification) is an important concept in Rasashastra, it is said that every drug should be subjected to Shodhana before its internal use and Mercury is no exception. Owing to its origin or other causes, Mercury is likely to be associated with different types of impurities of various degrees. Though many Doshas are attributed to Mercury Naga (Lead), Vanga (Tin) Doshas are considered the major ones. With the help of advanced chemical analytical techniques, quantitative detection of lead and tin contents in Mercury is possible to-day. Chemical analysis for lead and tin contents in Mercury before Shodhana i.e. unprocessed and after Shodhana i.e. processed leads to conformation of Naga, Vanga Doshas in Mercury. At the same time efficacy of the purificatory methods can be assessed by observing the reduction in percentage of lead and tin content in processed Mercury. Keeping this idea in mind, the present study physico-Chemical Study of different methods of Parada Samanya shodhana was under taken. All Samanya shodhana methods were screened to find out the most easy, quickest method and four methods were selected for this study. During the pharmaceutical work, time consumption, yield, and cost were taken into account in each selected purificatory methods. Four purified samples of Mercury along with raw sample of Mercury were sent for chemical analysis to SASTRA University, Tanjavur and samples were analyzed by using Atomic absorption spectroscopy (AAS). Depending upon the practical observation and statistical analysis it is concluded that Naga and Vanga- lead and tin are same respectively. All purificatory methods are effective in reducing lead and tin content that contaminate Mercury. The fourth method which consisted of triturating Mercury with Nagavalli swarasa, Ardraka swarasa and Triksara is most efficacious, quick, economic and more yielding method among the four selected Samanya shodhan methods. Apart from the criteria of good yield, and economy the Hingulotta parada and second method in which Mercury is triturated with Sudha churna, Lasuna kalka, and Saindhava lavana are more viable methods.